Willingness to Donate and Preferences of Zoos/Safari Parks Visitors Toward Endangered Mammals Conservation - Sunkar, Arzyana; Rachmawati, Eva; Santosa, Yanto; Hasanah, Siti (Media Konservasi, 2022)
A person may contribute to the conservation of species through donations. The willingness to donate (WTD) to conserve endangered species can depend on many factors. This research aims to determine the willingness of visitors to Indonesia’s zoos and safari parks to make a donation for species conservation and identify the determinants of their WTD through preferences toward certain species. This research focused on 12 priority endangered mammals. The study began with a preliminary survey of 110 respondents in January 2020, followed by data collection in February 2020 involving 1011 adult visitors to zoos and safari parks in Java and Bali. Specifically, descriptive statistics in the form of percentages ere used to analyze the influence of preferences toward species conservation and amount of donation while considering individual characteristics such as gender, age, place of residence, occupation, and level of education. Our results confirmed that mammals, mega-herbivores and large carnivores are very popular among young adult visitors. Overall, the results demonstrated that visitors placed rhino, elephant and tiger as the three priority species to be conserved in terms of donation given. It is clear that these three charismatic species have a very high conservation value in the eyes of the people. Furthermore, the characteristics of species and the knowledge and psychological preferences of the visitors can contribute to the determination of the preference for the number of donations to certain wildlife species. Key words: charismatic species, conservation institutions, demographic characteristics, Indonesia, primate